Representation and Negotiation of Women Syar’i Hijab Shaff Hijrah Community Through Instagram - Mahanani, Prima Ayu Rizqi; Chairani Putri, Risky (KnE Social Sciences, 2019)
The emergence of hijrah community does not bring its members to abandon the old habits which are forbidden by religion necessarily. Especially for female members who continue to take selfies and self-existence on Instagram media. The aim of this study to analyze how the self-representation of women in the Hijrah community on Instagram media and the negotiations which carried out on the established discourse. This study uses an observation method on three Instagram account from informants which combined by open ended interviews. The informants who is chosen are three members of the Hijrah or Shaff community in Kediri, East Java who wears different Syar’i hijab, with chadar and without chadar. The discovery in this study are members of the Hijrah community are represented against dominant construction and creating religious identity according toheir own version. They reject the logic of appearance as a representation of faith. While the activity on Instagram recognized as unavoidableactivity even though it’s been decided to hijrah. Negotiations on religious discourse is also shown in how they make resistance identity, which is free to do activities that are commonly carried out by women without the headscarf of Syar’i. Keywords: Instagram; hijrah community; negotiation; syar’i hijab; representation, women.